PENGARUH RASIO PROFITABILITAS, AKTIVITAS, LEVERAGE, DAN ARUS KAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR - Fitriyani, Dona; Susyanti, Susyanti; Kuntaryanto, Oki (Widya Dharma Journal of Business - WIJoB, 2024)
The purpose of this research to examine the effect of profitability ratio, activity, leverage, and cash flow to financial distress at manufacturing companies listed on the Indonesia Stock Exchange in 2021. The population were manufacturing companies listed on the Indonesia Stock Exchange in 2021. Sampling using purposive sampling technique. The number of samples in this study was 99 companies. The analytical methods used include descriptive test, classical assumption test including normality test, multicollinearity test, heteroscedasticity test, and hypotheses testing using multiple linier regression analysis method, simultaneous test, partial test, and test of the coefficient of determination. The results showed that profitability ratio and cash flow had a negative and significant effect to financial distress, leverage had positive and significant effect to financial distress, while activity had no effect to financial distress.